2019
DOI: 10.1038/s41467-019-13535-1
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution label-free 3D mapping of extracellular pH of single living cells

Abstract: Dynamic mapping of extracellular pH (pHe) at the single-cell level is critical for understanding the role of H+ in cellular and subcellular processes, with particular importance in cancer. While several pHe sensing techniques have been developed, accessing this information at the single-cell level requires improvement in sensitivity, spatial and temporal resolution. We report on a zwitterionic label-free pH nanoprobe that addresses these long-standing challenges. The probe has a sensitivity > 0.01 units, 2 ms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 44 publications
(61 reference statements)
0
82
0
Order By: Relevance
“…The data sources include a diversity of taxonomic groups including green algae, diatoms, cyanobacteria, chromista algae, and yellow-green algae from freshwater or marine environments, and the size of these species ranges from a few micrometers (e.g., Thalassiosira weissflogii ) 20 to hundreds of micrometers (e.g., Coscinodiscus wailesii ( 9 , 10 ) and Odontella sinensis ( 8 )). The studied samples include individual cells 8 , 9 , 20 and cell aggregates/colonies.…”
Section: Data Sources and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data sources include a diversity of taxonomic groups including green algae, diatoms, cyanobacteria, chromista algae, and yellow-green algae from freshwater or marine environments, and the size of these species ranges from a few micrometers (e.g., Thalassiosira weissflogii ) 20 to hundreds of micrometers (e.g., Coscinodiscus wailesii ( 9 , 10 ) and Odontella sinensis ( 8 )). The studied samples include individual cells 8 , 9 , 20 and cell aggregates/colonies.…”
Section: Data Sources and Methodsmentioning
confidence: 99%
“… 8 , 21 Some studies employed fluorescence pH dyes 20 or monitored pH sensitive extracellular reactions, 22 and one recent work used a novel pH nanoprobe. 10 Concentration gradients of both pH and O 2 in the phycosphere were reported for cell aggregates/colonies in some studies, but the data are rare for microalgae simply due to technical limitations in spatial resolution. The data we compiled in Figure 1 were those measured within the phycosphere, but the exact distances of the measurement points from the cell membrane are unknown.…”
Section: Data Sources and Methodsmentioning
confidence: 99%
“…Stimuli-responsive release of nanomedicines is based on the specific microenvironment of tumor tissue, which not only enables maximum release of drug into tumor tissue, but also reduces damage to normal tissue [31] 1 . Herein, we tested the drug-release efficiency of the nanomedicines in a simulated tumor microenvironment.…”
Section: Stimuli-responsive (Ph) Drug-release In Vitromentioning
confidence: 99%
“…Its biological application was thus first reported by Korchev et al (1997), who observed live cultured cells under liquid conditions. Since then, SICM has been used to obtain images of the surface information of different cultured cells (Korchev et al 2000;Pastré et al 2001;Happel et al 2003;Gorelik et al 2004;Gorelik et al 2006;Chen et al 2013;McKelvey et al 2014;Zhou et al 2016Zhou et al , 2017Simeonov and Schaffer 2019;Zhang et al 2019;Takahashi et al 2020).…”
Section: Introductionmentioning
confidence: 99%